THE EFFECT OF TRAINING AND DEVELOPMENT PROGRAM AND WORK CHARACTERISTICS ON EMPLOYEES PERFORMANCE IN MINISTRY OF RELIGION OFFICE IN SOUTH MINAHASA DISTRICT - Torar, Pricilia Natalia (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Employees are the big asset of organization. Employee Performance has big effect to organizaional performance.The role of agencies that includes all activities undertaken are always aiming to achieve maximum results with available resources, requiring the role of human resources that exist in the institution concerned. Human resources have a very big role because human activities in these institutions so as to make the company has the ability to achieve its objectives. Agencies also need to provide guidance as well as serious attention and sincerely to humans, so there is a balance between the two and the workers will feel used his ability as a worker. Training and Job Characteristic have significant influence on employee performance. leader in Ministry of Religious Affair Office of Christian in South Minahasa Regency should pay attention to Training and Job Characteristic have significant influence on employee performance. Keywords: training, job characteristic, employee performance